The Role of Career Guidance and Counseling Services in Helping Learners Identify Their Interests and Talents - Wulan Rada; Lisa Azzahra Tawir; S. Suci; Nur Aqiqah Putri; Nur Afiah Tawakkal; Ramli Ely (Golden Ratio of Data in Summary, 2026)
Students are expected to have a clear understanding of their interests and talents as a foundation for determining their career direction. However, many students still cannot fully recognize their potential, which makes it difficult for them to plan their future careers. This study aims to describe the role of career guidance and counseling services in helping students understand and develop their interests and talents. The research employed a descriptive qualitative approach, drawing on relevant national and international journal articles. The findings indicate that career guidance and counseling services play a significant role in helping students identify their potential through mentoring, interest and talent assessments, and the provision of educational and occupational information. These services contribute to deeper self-understanding, enabling students to plan and make career decisions more accurately and realistically. Therefore, the continuous implementation of career guidance and counseling services is essential to support students' optimal career development.